NARATOLOGI DALAM KRITIK SASTRA ARAB - Ikhwan Ikhwan; Wahyu Mustika Rani (PT. RANESS MEDIA RANCAGE, 2026)
Contemporary Arabic literary criticism has undergone a paradigm shift from subjective assessment to the search for systematic objective standards. This study aims to map the position and urgency of narratology as an instrument of criticism in the Arabic literary landscape. The research method used is qualitative with a descriptive analysis model through literature study. Primary data sources include fundamental works on narratology by Gérard Genette, Seymour Chatman, and Mieke Bal, as well as supporting literature on the development of narratology in the Arab world. The results of the study show that narratology occupies a strategic position in Arabic literary criticism, capable of uniting various forms of narrative into a single standardized scientific system, despite facing terminological challenges in the adaptation process. and the complexity of narratology offered by Genette, Chatman, and Bal has significant urgency in revealing structural and ideological dimensions that are often overlooked in traditional studies, both in classical texts and in the experimental aesthetics of modern novels. Thus, narratology provides a methodological answer to the need for a “structure” standard without discarding the unique characteristics and identity of Arabic literature.